PENINGKATAN KETERAMPILAN MENULIS TEKS NARASI MENGGUNAKAN PENDEKATAN CTL BERBANTUAN MEDIA GAMBAR SERI DI KELAS III SDN 16 PAGAMBIRAN - Nanda Ocktaviani, Cerillia; Azmi Alwi, Nur; Suriani, Ari; Adrias (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve students’ narrative writing skills through the application of the Contextual Teaching and Learning (CTL) approach assisted by serial picture media in Grade III of SDN 16 Pagambiran. The background of this research is the low ability of students in writing narrative texts, especially in organizing ideas, structuring stories, and using proper spelling and punctuation. This study utilized a Classroom Action Research (CAR) design that integrated qualitative and quantitative methods, implemented in two cycles involving planning, implementation, observation, and reflection. The participants were 28 third-grade students. The results demonstrated a significant enhancement in students’ writing skills. In Cycle I, students’ average score increased but had not yet reached the success indicator. In Cycle II, the improvement became more significant, with the average score reaching a good category. Students were able to develop story content, structure narrative texts properly, and improve language use as well as spelling and punctuation. In addition, students’ learning activities and attitudes also improved significantly. Therefore, the CTL approach assisted by serial picture media is effective in enhancing students’ narrative writing skills.